Membangun Branding Dalam Menciptakan UMKM Startup - Septemberizal Septemberizal; Rinaldo Rinaldo; Tria Patrianti; Septi Wulandari Chairina (Jurnal Pengabdian Masyarakat Nusantara, 2023)
One of the important elements that must be considered in starting a business is the brand. Brand image has the meaning of an image of a product in the minds of consumers. Everyone will have the same image of a brand. Through Brand Image consumers are able to recognize a product, evaluate its qualy, reduce purchase risk and gain experience and satisfaction from certain product differentiation. There are problems faced by Small Medium Enterprises (SME) assisted by Amil Zakat agency (Baznas) in Universitas Muhammadiyah Jakarta. Based on the interviews conducted, the problems identified were the Brand building itself.  The SMME focuses on sales strategy. It is found that the solution offered is to overcome the said problem by providing assistance and counseling about the importance of building the brand so that it can provide added value and have an impact on increasing profits which will ultimately build reputation and create growth opportunities for SMEs.